Adam - Frank, Jacquelyn (Frank, Jacquelyn. Nightwalkers., 2011)
When Adam, the only lover to fulfill her both sexually and intellectually, returns after four hundred years, Jasmine, a Nightwalker vampire, helps him to bring down their most vicious enemy while yielding to their mutual passion.